DABCO-catalyzed silver-promoted direct thiolation of pyrazolones with diaryl disulfides - Akkharaphong Thupyai (2019)
© 2018 The Royal Society of Chemistry. A highly efficient protocol for a direct thiolation of N-substituted pyrazolones with diaryl disulfides is described. Using a combination of DABCO and silver(i) acetate, the C-S bond formation proceeds smoothly at room temperature under mild and easy to handle conditions. This synthetic strategy offers a convenient and direct modification of antipyrine and other pyrazolone substrates, giving a series of aryl sulfide-substituted pyrazolone products in moderate to excellent yields.